Tingkat kepuasan terhadap pembersih gigitiruan pada pengguna gigitiruan di Rumah Sakit Gigi Mulut Fakultas Kedokteran Gigi Universitas Hasanuddin Satisfaction level about denture cleanser of denture wearers on the Dental Hospital Faculty of Dentistry Hasanuddin University - Reisintiya Reisintiya; Eri H. Jubhari (Journal of Dentomaxillofacial Science, 2013)
Patient dissatisfaction occurs in both developing and developed countries. Patient satisfaction is a very subjectivething; it is difficult to measure, changeable and there are many factors influencing person’s level of satisfaction. Betelleaf (Piper betle)has many benefits to health. Betel leaf is a natural ingredient that is known to contain phenols andvolatile oil which gives the most distinctive smell in the betel leaf. Solution of betel leaf can also be used as amouthwash and denture cleansers. In addition, there are several kinds of commercially available cleanser, such asalkaline peroxide. This study was aimed to know the level of denture users’ satisfaction in Dental Hospital, Faculty ofDentistry, Hasanuddin University against denture cleanser. By using an observational analytic method, sample of thisstudy were all removable denture users inserted in April to May 2013. Polident and betel leaf extract of 20% were usedas cleansers. Data were collected by questionnaires and processed by chi-square test using SPSS v.21.0. The levelsatisfied of patient using alkaline peroxide was 100; compared with betel leaf extract of 20% was dissatisfied (p=0.000). It was concluded that alkaline peroxide denture cleanser gives a different sense of satisfaction significantlycompared with the betel leaf extract.